Knowledge and power: Curricular policy's evolution and paradoxical relationship with practice in Shanghai. Issue 10 (24th August 2022) - Huang, Zhongjing
Abstract: Curriculum, as an expression of legitimate knowledge, should be seen as something political rather than technical, that is, as the result of complex power relations and struggles among identifiable stakeholder groups. In Shanghai, curricular reform, which traditionally assumes the crucial task of cultivating responsible citizens, has sought to situate education as an instrument of ideological indoctrination, at least to some extent. However, due to economic and social changes, such as those related to globalisation and modern ideals of educational development, curricular reform has undergone remarkable ideological changes that have given rise to paradoxes between policy and practice. This article explores the evolution of curricular policy and the ways in which it emerges in a paradoxical relationship to practice by analysing the relationship between curricular knowledge and power in Shanghai.